An ecological network analysis of the structure, development and sustainability of China's natural gas supply system security. (February 2017) - Shaikh, Faheemullah; Ji, Qiang; Fan, Ying
Graphical abstract: Highlights: China's natural gas supply system security policy is assessed using ENA. China's natural gas supply system is tending towards complexity. Resource utilization of the China's natural gas supply system has reduced. Flexibility and diversity of China's natural gas supply system has increased. Sustainability of China's natural gas supply system has reduced. Abstract: Mitigating the impacts of climate change and ensuring energy supply security has compelled China's policy makers to maximise the use of alternative and low carbon fuels. Use and production of natural gas (an energy source with low carbon emissions) has experienced remarkable growth in China during the last decade, making China the third largest consumer and importer in the world. This study applied a powerful system-oriented ecological network analysis (ENA) technique to study China's natural gas policies as they pertain to guarantee supply security. Several indicators based on the ENA were measured to analyse the degree of connectivity, the contributions of different compartments, resource utilisation (aggradation), development (ascendancy) and sustainability of China's natural gas supply system. It was found that China's source and route diversification policy have caused the natural gas supply system to exhibit considerable network complexity, demonstrating the high level of development, flexibility and diversity of China's natural gas supply system. However, the policy also has caused a decrease in the aggradation and sustainability from the perspective of an ecological system network. The most important compartments in terms of their contribution to China's natural gas supply system were found to be domestic natural gas production and transit compartments.